The Effect Of Local Government Expenditure On Poverty And Unemployment In Bireuen District - Nunun Khairina; Annisa Fitri; Sri Rahayu; Rahmat Hidayat (STMIK Indonesia Banda Aceh, 2025)
This study aims to determine the influence of regional government expenditure on poverty and unemployment in Bireuen Regency. The research method used is a quantitative approach with simple linear regression analysis, including classical assumption tests and hypothesis testing, processed using IBM SPSS 25. The data used in this study are secondary time series data for a 10 year period, from 2014 to 2023. The results of the study show that regional government expenditure partially has a significant effect on poverty, with a t value (3.023) > t table value (2.306) and a significance level of 0.016 < 0.05. In addition, regional government expenditure also has a significant effect on unemployment, with a t value (4.059) > t table value (2.306) and a significance level of 0.004 < 0.05. The influence of regional government expenditure on poverty is 42.3%, while the remaining 57.7% is influenced by other variables outside this study. Meanwhile, the influence of regional government expenditure on unemployment is 67.3%, with the remaining 32.7% influenced by other factors not examined in this research.